Discovery of the genus Dioedus LeConte, 1862 from China, with description of a new species (Coleoptera: Tenebrionidae) - Jiang, Ri-Xin; Wang, Ji-Shen; Wang, Shuo (Zootaxa, 2020)
The genus Dioedus LeConte, 1862 (Coleoptera: Tenebrionidae: Phrenapatinae: Penetini) is recorded from China for the first time. A new species Dioedus liuhaoyii Jiang, Wang & Wang sp. nov. is described from Henan Province, China. Habitus and diagnostic features of the adult of the new species are described and illustrated.